Reduced autophagy efficiency induces innate immune activation leading to neurodegeneration. Issue 6 (3rd June 2019) - Shukla, Arvind K.; Giniger, Edward
ABSTRACT: Macroautophagy/autophagy and innate immunity are central processes in neurodegeneration, but it has been unclear whether they work independently or in combination to assault the neuron. We recently demonstrated that reduced efficiency of autophagy causes hyperactivation of innate immunity, which in turn is necessary and sufficient for loss of dopaminergic neurons in a Cdk5-mediated model of degeneration in Drosophila . Genetically restoring autophagy, or reducing innate immune activation, rescues the dopaminergic neuron loss that occurs due to altered Cdk5 activity. This work revealed an alliance of innate immunity and autophagy that causes neuron loss in Cdk5-mediated neurodegeneration.